ACTUALITATEA MESAJULUI POETIC AL LUI ION VATAMANU - RĂILEANU, critic literar, Vitalie (BIBLIOPOLIS, 2020)
The author highlights the poetic works of Ion Vatamanu (1 May 1937, Costiceni, Hotin County – 9 August 1993, Chişinău) – poet, publicist, translator, chemist scholar, politician. Ion Vatamanu was an authentic painter of poetry. The poet is a veritable painter of the nuances in poetry, an artist of a great refinement of the thought and intelectuality, which is expressed often by cold blasts of memories. It’s dificult to define this poet, he could be named Voltaire of Bessarabian modern poetry. Beyond any doubt, we can say that in the beginning of the third millennium we miss a live poetry of poet Vatamanu, full of mystery, new horizons, discoveries.